K-Pop dan Fandom Laki-Laki: Pengungkapan dan Identitas Diri Pecinta Boyband Korea - Sonia Ratna Juwita; Zainal Abidin; Yanti Tayo (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The research entitled "Identity and self-disclosure of a fandom (phenomenological study of the identity and self-disclosure of male fandoms who love Korean Boyband in Karawang)" has an identification problem that seeks to find meaning in Korean Boyband for a man. fandoms who love Korean boybands, looking for motives to become a fandom of Korean boyband lovers, as well as finding out how to experience communication to become a male fandom of Korean boyband lovers. This is interesting because around the researcher, there are already many male fandoms who like Korean boybands, where not many know the reasons they like Korean boybands so that researchers want to examine the construction of the meaning of male fandoms who love Korean boybands. This study uses a qualitative method and a phenomenological approach, because in this study the researcher examines a phenomenon with the aim of finding the meaning of male fandom who loves Korean boybands. The research is going well, the researcher must examine it in depth so that the informant will provide true information. The theory used is Alfred Schutz's phenomenological theory which is the basis for researchers in conducting this research. Keywords: Phenomenology, Male Fandom, Meaning